Student Perception of Waste Management in Petra Christian University as a Green Campus - Alfred, William; Nugraha, Richard Cahya; Cindy, Cindy; Budhiyanto, Aris (Proceedings of the International Conference on Green Technology; Vol 9 No 1 (2018): Proceeding of the 9th International Conference on Green Technology 2018, 2019)
The development of green building issue that refers to environmental friendly building has significant impact around the world, as    it is in Indonesia. Petra Christian University responded that issue by starting the green campus movement since 2010. The goal of this movement is to engage all students to be more care about environmental sustainability including waste management. The aim   of this study is to determine the students’ perception about the waste management in Petra Christian University. In order to understand students’ perception toward the waste management, a questionnaire was used. The result of this study is waste management need to be improved as about 40% of the respondents indicate that they do not know about the waste management in Petra Christian University.